2009
DOI: 10.1038/eye.2008.393
|View full text |Cite
|
Sign up to set email alerts
|

Descemet membrane endothelial keratoplasty (DMEK) for Fuchs endothelial dystrophy: review of the first 50 consecutive cases

Abstract: Purpose: To evaluate the clinical outcome and complications of Descemet membrane endothelial keratoplasty (DMEK), using Descemet-stripping endothelial keratoplasty (DSEK) as a back-up procedure, in the management of Fuchs endothelial dystrophy. Design: Non-randomised prospective clinical study. Methods: The first fifty consecutive eyes that underwent DMEK, that is, transplantation of an isolated donor Descemet membrane carrying its endothelium, for Fuchs endothelial dystrophy were evaluated. In all eyes, the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
142
0
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(157 citation statements)
references
References 26 publications
(42 reference statements)
5
142
0
8
Order By: Relevance
“…[46][47]50,76,97,[103][104][105]123 Tourtas et al found that central corneal thickness reduced from 652+/-92 microns to 517+/-45 microns after DMEK and from 698+/-137 microns to 618+/-66 microns after DSAEK. 123 This difference in thickness is one explanation for the improved visual outcomes.…”
Section: Reducing Graft Thicknessmentioning
confidence: 99%
See 1 more Smart Citation
“…[46][47]50,76,97,[103][104][105]123 Tourtas et al found that central corneal thickness reduced from 652+/-92 microns to 517+/-45 microns after DMEK and from 698+/-137 microns to 618+/-66 microns after DSAEK. 123 This difference in thickness is one explanation for the improved visual outcomes.…”
Section: Reducing Graft Thicknessmentioning
confidence: 99%
“…133 Faster and improved visual rehabilitation has been achieved with DMEK. 46,48,70 In the largest series of DMEK reported to date, 41% eyes without ocular comorbidity attained BCVA of 20/20 or better at six months.…”
Section: The Interface In Dmekmentioning
confidence: 99%
“…Nessa técnica cirúrgica, a córnea receptora é preparada com o "stripping" da mesma forma que o DSEK/DSAEK, mas a córnea doada consiste apenas da membrana de Descemet e endotélio, sem estroma associado. Os resultados visuais são superiores e com uma reabilitação visual mais rápida (19)(20)(21) . Mas é uma técnica cirúrgica mais difícil, com número maior de complicações nas primeiras publicações (19)(20)(21) .…”
Section: Introductionunclassified
“…Os resultados visuais são superiores e com uma reabilitação visual mais rápida (19)(20)(21) . Mas é uma técnica cirúrgica mais difícil, com número maior de complicações nas primeiras publicações (19)(20)(21) . Poucos cirurgiões no mundo realizam essa técnica com bons resultados e baixo índice de complicações.…”
Section: Introductionunclassified
“…Review of several studies done in North America identified Fuchs' corneal dystrophy as the second most common www.jors.js.iknito.com indication for keratoplasty (15%) ranking second after pseudophakic bullous keratopathy (PBK) (38%) [17][18][19] . Significant proportion of patients with Fuchs dystrophy remain compensated for life and will benefit from cataract surgery to improve their vision, hence the need to minimize further damage on their corneas during cataract surgeries.…”
Section: A Fuchs Corneal Dystrophymentioning
confidence: 99%